Mild-aortic syndrome: a cause of recurrent abdominal pain - Yubbu, Putri; Abdul Latiff, Haifa; Sing, Alan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Mid-aortic syndrome (MAS) is a rare clinical entity that is characterized by coarctation involving the distal thoracic and/or abdominal aorta and its major branches accounting for 0.5–2% of all cases of coarctation of the aorta (1). Renovascular hypertension can be a significant sequelae - it is the main symptomatic presentation of this disease among children and adolescents. We describe a 9-year-old girl who presents with recurrent abdominal pain and symptomatic hypertension. Due to significant left ventricular systolic dysfunction and uncontrolled hypertension, percutaneous balloon angioplasty was performed to treat the coarctation. To our knowledge, this is the first reported case of MAS in Malaysia. This case report highlights the clinical presentation, the role of computed tomography angiogram (CTA) in the diagnosis and current options in the management of MAS.